ENTREPRENEURIAL ORIENTATION AMONG MSMES IN BALI’S ECONOMIC RECOVERY DURING COVID-19 PANDEMIC - Carina, Tiara; Mentari, Ni Made Indah; Putra, I Dewa Made Arik Permana; Sari, Putu Melani Gita; Dewi, Putu Tasiya Purnama (Graduate Program of Universitas Tarumanagara, 2023)
Bali is the most affected region by the tourism sector during pandemic with economic growth of -9.31% in 2020. The economic difficulties faced by the community, especially those who used to work in the tourism sector, made people turn to the Micro, Small and Medium Enterprises (MSME) sector in order to continue to earn income in the midst of uncertain conditions during the pandemic. This research reviewed some literature related to the role of MSMEs in Bali’s economic growth during pandemic. The results show that during the economic contraction, MSMEs have a big role in revitalizing the Bali economy. The increase in the number of MSMEs in Bali during pandemic implies that there are still many Balinese people who have a high entrepreneurial orientation. The good performance of MSMEs with a good entrepreneurial orientation is able to support Bali economy during pandemic which has experienced a drastic decline.